Pengaruh Dividend Payout Ratio, Risiko Keuangan, Nilai Perusahaan, dan Ukuran Perusahaan terhadap Perataan Laba (Studi pada Perusahaan Manufaktur Sektor Industri Dasar dan Kimia Listing di Bursa Efek Indonesia) - Ibnu Abni Lahaya (AKUNTABEL, 2017)
The purpose of this research is to analyze and test the influence; The effect of dividend payout ratio on income smoothing action, financial risk to profit smoothing action, company value to earnings smoothing action, and firm size to earnings smoothing action. This research was conducted at manufacturing company of basic and chemical industry sector which listed in Bursa Efek Indonesia in period 2013-2015 by using purposive sampling. Simultaneously Dividend Payout Ratio, Company Risk, Company Value, and Company Size have significant effect to income smoothing action, with F significance value equal to 0,015 (0,05) and R2 coefficient of determination equal to 34,7% or in other words equal to 65 , 3% influenced by other variables not described in this study.Keywords: Dividend Payout Ratio, Purpose Sampling, Flattening Earnings.